SMART QR CODE–ENABLED TRANSPORTER AUTHENTICATION AND PROOF OF DELIVERY SYSTEM WITH REAL-TIME GPS TRACKING - Dr Hanmant N Renushe; Dr Arun R. Dhang; Dr Vishal P. Deshmukh; Dr Abhijit A Patil; Dr Prasanna R. Rasal (The Bioscan, 2026)
The logistics sector faces persistent challenges such as unauthorized transporter access, proxy-based loading, and disputes regarding proof of delivery. Traditional systems lack real-time authentication and monitoring, leading to inefficiencies and security risks. This research proposes a Smart QR Code– Enabled Transporter Authentication and Proof of Delivery System integrated with real-time GPS tracking. The system utilizes QR.io for dynamic QR generation, WhatsApp API for communication, Pabbly Connect for workflow automation, Effebot API for voice verification, and GPS technology for continuous vehicle tracking. Unique, time-bound QR codes authenticate transporter personnel at loading and delivery points, while GPS tracking provides live location updates throughout transit. Experimental evaluation with 100 users across multiple scenarios shows a 92% reduction in fraud, 98.5% authentication accuracy, 97% delivery success rate, and enhanced transparency through real-time tracking. The system significantly improves logistics security, accountability, and operational efficiency.